SMART GOVERNANCE IN THE DIGITAL ERA: MODELS AND GLOBAL PRACTICES - M. Kafrawi Al-Kafiah Samsu; Thalita Rifda Khaerani (VISIONER : Jurnal Pemerintahan Daerah di Indonesia, 2025)
Smart governance has emerged as a critical paradigm in the digital era, redefining how governments interact with citizens, manage data, and deliver public services. This study conducts a structured literature review to synthesize global models and practices of smart governance implemented across different socio-political contexts. The analysis explores how digital technologies such as artificial intelligence, big data, and blockchain reshape administrative processes and policy innovation. Findings reveal that successful models of smart governance rely on transparency, inter-agency collaboration, and citizen participation as key pillars of sustainability. Comparative studies demonstrate that nations adopting integrated e-government systems achieve higher efficiency and responsiveness in public service delivery. However, the literature also identifies persistent challenges, including digital divides, cybersecurity threats, and regulatory fragmentation. This review emphasizes that technological advancement alone is insufficient without institutional readiness and inclusive digital policies. The study contributes to a comprehensive understanding of how global practices can inform adaptive governance frameworks in emerging economies. Theoretical insights highlight the convergence of digital transformation and governance theories in fostering participatory and data-driven public administration. Ultimately, this research provides a foundation for future empirical studies seeking to evaluate the effectiveness and scalability of smart governance initiatives worldwide.